Active Learning with Interactive Whiteboards: A Literature Review and a Case Study for College Freshmen - Robert Schroeder (Communications in Information Literacy, 2008)
A well-designed classroom that includes appropriate technology can inspire and support successful instructional design. Interactive whiteboards (IWBs), an example of this technology, have been adopted in Great Britain, primarily in primary and secondary schools. While the literature anecdotally suggests that there are benefits associated with using them in classroom instruction little has been written about their application and efficacy in higher education. The author describes an exercise designed for college freshman, and discusses the benefits of the group work and active assignments engendered by the IWB.